RANCANG BANGUN APLIKASI KASIR BERBASIS WEB PADA TOKO GOPRAN STORE PAYUPUTAT - Jimmie; Agung Repian (STKIP Subang, 2024)
The rapid development of information technology, especially in the field of software and computer-based information systems, has had a significant impact on various sectors of life, including the business world. The use of information technology such as websites and web-based applications increasingly dominates daily activities, including business processes and transactions. However, at the Gopran Store, the transaction recording system which still uses paper media causes various problems, such as errors in recording, damage or loss of documents, as well as inefficiency in the time required for the transaction process. To overcome this problem, this research aims to design and build a web-based cashier application that can simplify the transaction process, increase calculation accuracy, and minimize errors in recording payment receipts. With this application, it is hoped that Gopran Store can increase operational efficiency, speed up the transaction process, and reduce the risk of losses caused by manual recording errors. It is hoped that this research can contribute to advancing information technology systems in the field of small retail businesses.